Item Quality Analysis of Physics Concept Understanding Test with Rasch Model - Kurniawan, Aris; Istiyono, Edi; Naba, Sul Daeng (JIPF (Jurnal Ilmu Pendidikan Fisika), 2024)
This study aims to determine the quality of physics concept understanding test items on the topic of electromagnetic waves based on estimation of item fit, item difficulty level estimation, and item reliability estimation. The research sample consisted of 298 eleventh-grade science students from several public high schools in Central Kalimantan province. The results of data analysis using the Rasch model with the aid of QUEST software showed that all items were fit or valid, with INFIT MNSQ values ranging from 0.77 to 1.33. The item reliability was 0.98, categorized as excellent, and the test participant reliability was 0.25, categorized as weak. The difficulty level of the test items was categorized into three: 5 items were difficult, 5 items were moderate, and 5 items were easy. Furthermore, based on the analysis using OUTFIT t values, one item was discarded and could not be used as a test instrument because it had an OUTFIT t value greater than 2.